Nanoparticles in ocular applications and their potential toxicity - Yang, Cao; Yang, Junling; Lu, Ao; Gong, Jing; Yang, Yuanxing; Lin, Xi; Li, Minghui; Xu, Haiwei (Frontiers in Molecular Biosciences, 2022)
Nanotechnology has been developed rapidly in recent decades and widely applied in ocular disease therapy. Nano-drug delivery systems overcome the bottlenecks of current ophthalmic drug delivery and are characterized with strong biocompatibility, stability, efficiency, sustainability, controllability, and few side effects. Nanoparticles have been identified as a promising and generally safe ophthalmic drug-delivery system based on the toxicity assessment in animals. Previous studies have found that common nanoparticles can be toxic to the cornea, conjunctiva, and retina under certain conditions. Because of the species differences between humans and animals, advanced in vitro cell culture techniques, such as human organoids, can mimic the human organism to a certain extent, bringing nanoparticle toxicity assessment to a new stage. This review summarizes the advanced application of nanoparticles in ocular drug delivery and the potential toxicity, as well as some of the current challenges and future opportunities in nanotoxicological evaluation.